2019
DOI: 10.1371/journal.pone.0209425
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal carriage of antibiotic resistant Acinetobacter baumannii among newborns hospitalized in Moroccan neonatal intensive care unit

Abstract: This study was conducted in order to assess the acquisition rate of Acinetobacter baumannii by newborn screening, on admission and during the discharge process of neonatal intensive care unit. (NICU). Furthermore, we investigated risk factors for potential colonization and molecular epidemiology of isolated resistant bacteria. This prospective study was conducted in the neonatal unit of Hassan II University Hospital of Fez from February 2013 to July 2015. During this period, all consecutive admitted neonates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Moreover, this corresponds to the results published in our previous manuscript which shows that all isolates of A . baumannii harbored bla OXA-23 and bla OXA-51 but no bla OXA-48 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this corresponds to the results published in our previous manuscript which shows that all isolates of A . baumannii harbored bla OXA-23 and bla OXA-51 but no bla OXA-48 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of AR of several A. baumannii isolates collected from different intensive care units revealed high resistance to the most commonly used antibiotics [ 16 , 17 ]. Several studies reported high carbapenem, aminoglycoside and colistin resistance of A. baumannii strains [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Table 1 ). The carbapenem resistance was associated with the overexpression of OXA-51 [ 32 ] and OXA-23 [ 33 , 34 ] class D carbapenemases as well as of metallo-β-lactamases (MBLs) [ 35 ].…”
Section: Ar Profiles Of a Baumannii Strainsmentioning
confidence: 99%
“…and Pseudomonas spp. increased in number, with alarmingly high rates of resistance [161][162][163][164][165]. Even rare species of CP nonfermenters were reported [166].…”
Section: Sub-saharan Africamentioning
confidence: 99%